2005
DOI: 10.1111/j.1365-2230.2004.01691.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous administration of collagen-polyvinylpyrrolidone down regulates IL-1beta, TNF-alpha, TGF-beta1, ELAM-1 and VCAM-1 expression in scleroderma skin lesions

Abstract: In this study the effect of collagen-polyvinylpyrrolidone (collagen-PVP) vs. triamcinolone acetonide (Triam) in scleroderma (SSc) skin lesions was evaluated. Ten SSc patients were treated weekly with subcutaneous injections of 0.2 mL Triam (8 mg/mL) or 0.2 mL collagen-PVP (1.66 mg collagen). Skin biopsies were obtained from lesions before and after treatment. Tissue sections were evaluated by histology and immunohistochemistry (ELAM-1, VCAM-1, IL-1beta, TNF-alpha, TGF-beta1 and PDGF). The corticoid-treated gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 7 publications
(16 reference statements)
4
31
0
Order By: Relevance
“…These results corroborate the findings of several studies that topically applied Collagen-PVP and concluded that this drug enhances collagen production and organized CD in the ECM, as previously shown in the skin [1, 10, 31]. Similarly, our results corroborate the findings of other studies that reported decreased fibrosis and improved collagen organization after treating pulmonary [16, 27], tracheal [24], hepatic, and renal [28] fibrotic lesions and glaucoma [32] with PFD.…”
Section: Discussionsupporting
confidence: 91%
“…These results corroborate the findings of several studies that topically applied Collagen-PVP and concluded that this drug enhances collagen production and organized CD in the ECM, as previously shown in the skin [1, 10, 31]. Similarly, our results corroborate the findings of other studies that reported decreased fibrosis and improved collagen organization after treating pulmonary [16, 27], tracheal [24], hepatic, and renal [28] fibrotic lesions and glaucoma [32] with PFD.…”
Section: Discussionsupporting
confidence: 91%
“…The amount of solution was chosen empirically and was injected only in and around the lesion and sprayed over the surface of the ulcer. This decision was supported by previous reports of cases in which collagen-PVP treatment was successfully used (injecting intramuscularly and subcutaneously for patients with rheumatoid arthritis and scleroderma, and application to the surface of dermatological ulcers secondary to venous insufficiency [4][5][6], as well as in the case described in our previous publication [3]). The patient consented to the use of the biological compound for treatment.…”
Section: Case Presentationsupporting
confidence: 71%
“…This is possibly accomplished by downregulating proinflamamatory cytokines and adhesion molecules such as intercellular adhesion molecule-1, vascular cell adhesion molecule-1, interleukin-1beta, tumour necrosis factor-alpha and platelet-derived growth factor (3,(7)(8)(9)(10). Intralesional injection of collagen-PVP once a week for one to three months into human hypertrophic scars or scleroderma lesions diminishes pruritus, pain, erythema, volume and inflammatory infiltrates (5,11). This product makes tissue architecture resemble normal skin and modifies the histological and biochemical pattern of fibrosis without changing the total collagen content (12).…”
Section: Discussionmentioning
confidence: 99%
“…Local drug delivery strategies may provide for the development of more successful OA treatment outcomes that have potential to reduce local joint inflammation, reduce joint proteolysis, offer pain relief, and restore activities of daily living levels and diarthrodial joint function. For this reason, we have evaluated the effect of a γ-irradiated mixture of a telopeptidic porcine type I collagen and polyvinylpyrrolidone (polymerized-type I collagen), which has anti-inflammatory properties [14,15]. One percent polymerized-type I collagen addition to synovial tissue cultures from non-rheumatoid arthritis (RA) and RA does not induce any change in DNA concentration or metabolism.…”
Section: Open Access Https://scidocorg/ijbrrphpmentioning
confidence: 99%
“…The rationale to inject IA polymerized-type I collagen was based on the encouragement from previous experience related to the biodrug effects (anti-inflammatory and tissue regenerator effects) observed during the course of the treatment of hypertrophic scars, scleroderma (SSc) skin lesions and RA patients [14][15][16][17][18][19][20][21].…”
Section: Rationalementioning
confidence: 99%